INFORMATION COMPETENCE AS A BASIS FOR STUDENTS'SELF-REALIZATION: PRACTICAL EXPERIENCE - Losyeva, Nataliya M.; Kyrylenko, Nelya M.; Kyrylenko, Valerii V.; Kryzhanovskyi, Andrii I. (My University, 2021)
The article deals with the ways of developing students' information competence and examines its impact on self-realization of students. The importance of the formation and developmentof future teachers’ information competence in the paradigm of new approaches to higher education and its humanization is emphasized since information competence is one of the significant indications of their successful professional training. The correlation of competence with the personal characteristics of future teachers andtheir further potential for self-realization is analyzed. The concept of ‘information competence’ in the context of digitalization of modern education is considered. Education computer technologies software which was used in the course of the experimentalresearch aimed at the development of future teachers’ information competence is presented. In order to develop students' desire for self-realization, modern pedagogical software tools were used. A pedagogical experiment is described in the framework of which the students used the proposed software tools which boosted information competence and their desire for self-realization. To solve this dual assignment a special ‘Information and communication technologies of training’ course has been developed. The study of this special course involved fulfillment of creative tasks, presentation of students' own ideas and their employment in the course of pedagogical practice. Whileprocessing experimental data by statistical non-parametric methods, the main componentsinfluencing the students’ desire for self-realization have been identified. Data of changes these parameters in experimental groups are provided, the conclusion about the positive influence of the described approach both on the development of information competence, and self-realization of students has been made
ІНФОРМАЦІЙНА КОМПЕТЕНТНІСТЬ ЯК ОСНОВА САМОРЕАЛІЗАЦІЇ СТУДЕНТІВ: ПРАКТИЧНИЙ ДОСВІД
Keywords: information competence; digital society; education process; competence approach; self-realization